EFEKTIFITAS PEMBERIAN JUS MENTIMUN DAN BAWANG PUTIH TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS LUBUK MUDA - Carles Carles; Eliza Fitria; Betty Nia Rulen; Zurni Seprina; Reza Reza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Hypertension or high blood pressure is a chronic condition in which the blood pressure on the walls of the arteries increases. Uncontrolled hypertension can increase the chances of cardiovascular disease, including stroke, and is three times more likely to have a heart attack. Hypertension is not a disease caused by a single causative factor, but there are many factors that influence blood pressure, including heredity, gender, age, smoking, alcohol consumption, stress and sodium intake. The purpose of this study was to determine the effectiveness of giving cucumber and watermelon juice on blood pressure in hypertension patients in the working area of the Lubuk Muda Health Center. This type of research was a quantitative study with a research design that used a quasi-experimental research design with a sample of 30 people. Data analysis used paired t test analysis. The results showed that there was a statistically significant effect between giving Young Watermelon and Cucumber Juice (p values 0.027 and 0.000) on decreasing blood pressure. It is recommended that the Public Health Center socialize traditional interventions in order to reduce the mortality rate of hypertension. Keywords : Hypertension, cucumber juice, watermelon